Risk sharing or risk shifting? On the development of patient access schemes in the process of updating the national list of health services in Israel. (2nd November 2019) - Triki, Noa; Ash, Nachman; Porath, Avi; Birnbaum, Yair; Greenberg, Dan; Hammerman, Ariel
ABSTRACT: Background : Agreements between payers and pharmaceutical/medical device companies are widely implemented to address financial and clinical uncertainties. We analyzed the main characteristics of these agreements in Israel from 2011–2018. Research design and methods : We reviewed all agreements implemented during the study period. Information regarding the type of agreement, therapeutic indications, its time frame and the total budget involved are presented. Results : A total of 56 agreements were signed since 2011, of which 53 (95%) were financial-based and 50 (89%) referred to pharmaceuticals. The annual number of agreements increased from one in 2011 to 21 in 2018. The main therapeutic areas covered were: oncology (41%), hepatitis C (16%), neurology (11%), respiratory (9%), and cardiovascular (7%). The proportion of the annual budget allocated subject to these agreements increased accordingly from 3% in 2011 to 73% in 2018. The majority (63%) of the agreements were signed for 5 years, 9% were shorter-term and 20% have no time-limit. In 14 (44%) of the financial-based agreements implemented through 2017, the actual utilization exceeded the pre-specified threshold and the companies reimbursed the health-plans accordingly. Conclusions : The number of agreements and the allocated budget subject to these agreements increased substantially in recent years. Most agreements are financial-based that, in many cases, shifted the short-term financial risk from health-plans to the industry.